SPIRITUALITY AS PASSIONS OF THE HEART. AN EMPIRICAL STUDY INTO THE CHARACTER, CORE VALUES AND EFFECTS OF THE PASSIONS OF THE HEART OF GENERAL PRACTITIONERS - C.A.M. Hermans; L. Kornet (Acta Theologica)
There is growing interest in the spirituality of physicians, relating to burnout and emotional stress and in terms of dealing with their workload. The authors distinguish four different lines of research in this area and position their approach of the “passions of the heart” as a meta-intentional feeling for what is good and satisfying, which we derive from a phenomenological theory of feeling by Stephan Strasser (1977). Human beings are characterised by a transcendental openness that interpenetrates human feelings. Four markers of passions of the heart are identified: fulfilment, receptivity, life-organising power, and ethical nature. Based on these markers, the article distinguishes between concerns identified as passions of the heart, and other concerns. Four core values are identified in the concerns of general practitioners (GPs) studied: personal proximity, self-direction, the whole person, and giving all people access to the healthcare they need – specifically the vulnerable. Finally, the authors present the GPs’ testimonies, in which they voice that passions of the heart mitigate the effects of negative experiences (emotional stress and burnout) and inspire and motivate them in their work.